PAGI SAMPAI MALAM HARI: REPRESENTASI LATAR WAKTU DALAM CERITA ANAK INDONESIA - Apriliya, Seni; Hodidjah, Hodidjah; Kholifah, Umul (Diksi, 2020)
(Title: From Morning to Night: Representation of Time Settings in IndonesianChildren's Stories). This paper aims to describe the time setting of children's stories. The study uses content analysis methods with categorization, tabulation, and inference techniques. Research data sources are 10 children's stories compiled in a book entitled "Naskah Terbaik Lomba Menulis Cerita Anak Tahun 2015 (Best Manuscripts of Children's Story Writing Competition)". The book was chosen purposively because it represented the work of Indonesian children who won national writing competitions. The results showed that (1) the time setting in children's stories was dominated by certain times of the day, such as morning, afternoon, evening, and night; (2) there are several time settings based on month/season/year, time settings based on a person's life phase, time settingsbased on specific history/events, time settings that indicate the past, present, and future; and (3) found a very specific time setting: referring to certain hours, and referring to the position of the sun. Thus, the time setting in the story is represented in various forms. This shows the creativity of Indonesian children in their work.Keywords: children's stories, intrinsic elements, time setting.